Insecticidal Activities of Stem Bark Extracts from Vitex negundo L. against Tribolium castaneum (Herbst) - Chowdhury, NY; Islam, W; Khalequzzaman, M (Journal of Bio-Science, 2011)
Context: Medicinal plants contains some pesticidal activities that may control stored product insects. Objectives: To elucidate the insecticidal activity from the stem bark extracts of nishinda (Vitex negundo L.) and their toxicity against red flour beetle, Tribolium castaneum (Herbst) (Tenebrionidae). Materials and Methods: The powdered stem bark (250 g) was extracted with methanol (MeOH), ethyl acetate (EtOAc), acetone and chloroform sequentially. Solvents were evaporated using a rotary evaporator to obtained dry extract, weighed and re-dissolved in the same solvent from which they were extracted for bioassay. Red flour beetles were reared for the experiment in 500 ml beakers containing food medium and kept in a control temperature room (30 ± 0.50C). Residual film bioassay was used to evaluate the toxicity. The adult mortality of T. castaneum (CTC-12, FSS-II and KANO strains) was recorded after 24, 48 and 72 h, but for larvae, the mortality was recorded on 12th and 20th larval day after treatment. The mortality percentages were subjected to probit analysis. Results: The LD50 values for first through fourth instar larvae were more or less similar whereas, LD50 for fifth instar larva and adults were the lowest. Among the solvents, methanolic extracts elucidated more toxicity on both adult and larval insects. The degree of toxicity of the extracts according to solvents was MeOH>Pet spt.>acetone>EtOAc. The susceptibility order according to insect strains was FSS-II>CTC-12>KANO. Conclusion: The results suggest the presence of active toxic substances of nishinda acting after consumption or topical application on T. castaneum. Methanolic extracts of the plant provided the most potent and reliable control of the flour beetle. Key words: Vitex negundo; sovent extracts; toxicity; Tribolium castaneum DOI: 10.3329/jbs.v17i0.7103 J. bio-sci. 17: 63-70, 2009